Do Indian economic activities impact ASEAN-5 stock markets? - Teng, Kee Tuan; Yean, Siew Hwa; Soo, Y. Chua; Hooi, Hooi Lean (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examines the dynamic linkages of ASEAN-5 with India based on a multivariate framework. DCC-MGARCH model was used to assess the presence of contagion effects and herding behaviour, indicated by the dynamic conditional correlations. The var -Granger causality test was employed to capture the direction of dynamic volatility transmission at the short run. Findings showed that the dynamic correlation of ASEAN-5 stock markets with Indian economy is in par with the U.S. and Japan. The simultaneous sudden spike in Dynamic Conditional Correlation between India and ASEAN-5 and followed by immediate reversal to decreasing Dynamic Conditional Correlation in 2009 indicate a contagion effect and herding behaviour which coincided with European sovereign debt crisis. The immediate reversal back to decreasing Dynamic Conditional Correlation suggests that both countries are hardly contagious by external crisis. In the short run, there is no volatility spillover from Indian economic activities to ASEAN-5 stock markets but there is volatility spillover from stock markets of Indonesia and Singapore to Indian economic activities. Trade policies, economic crises and economic liberalisation play significant roles in shaping the structure of the dynamic volatility correlations between the studied markets. This study reveals that ASEAN-5 has become preferred markets for the diversification of stock portfolio for India in the short run.